Radiation enhancing effects of sanazole and gemcitabine in hypoxic breast and cervical cancer cells in vitro - Zeng, Yue-Can; Wu, Rong; Xiao, Yu-Ping; Xin, Yan; Chi, Feng; Xing, Rui; Xue, Ming; Wang, Nai-Qian (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Sanazole and gemcitabine have been proven clinically as hypoxic cell radiosensitisers. This study was conducted to determine the radiation enhancing effects of sanazole and gemcitabine when administered together at relevant concentrations into hypoxic human MCF-7 and HeLa cells. Material and methods : A 3-(4,5 dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) assay was used to evaluate the number of surviving cells. Cell cycle was determined by flow cytometry. Cell surviving fractions were determined by the standard in vitro colony formation assay. Results : The cell colony formation assay indicated that the radiosensitivity of hypoxic MCF-7 and HeLa cells was enhanced by sanazole or gemcitabine. The combination of the two drugs displayed significant radiation enhancing effects at the irradiation doses of 6, 8, and 10 Gy in both cell lines, which were arrested in the S phase. Conclusions : This study indicated that the co-administration of the two drugs may result in a beneficial gain in radiotherapy for hypoxic breast cancer and cervical cancer.